Penegakkan Hukum Bagi Pelanggar Lalu Lintas dengan Sistem Electronic Traffic Law Enforcement (ETLE) - Alamin, Patrick Assyauqi Lil; Rochmani, Rochmani (Universitas Batanghari Jambi, 2024)
The ETLE system is an attempt by law enforcement to use information technology to record infractions of the traffic laws and provide electronic support to maintain traffic safety and order. The goal of ETLE's introduction is to end unlawful collecting during the ticketing procedure by careless police personnel. The formulation of the research problem is how the ETLE mechanism handles traffic infractions, if it can successfully lower the amount of traffic infractions, what are the barriers to system implementation, and how the general public feels about system implementation. This research aims to analyze the ETLE mechanism in resolving traffic violations, whether the existence of an ETLE system can reduce the level of traffic violations, obstacles to implementing ETLE, and the public's views on implementing the ETLE system. The research method that will be used is empirical juridical. The data used was obtained through direct interviews between the author and respondents, documentation, and focused observations on case studies related to law enforcement for traffic violators using the ETLE system. The results of the research show that the ETLE mechanism in resolving traffic violations makes things easier for the police and the public who are ticketed, besides that the ETLE system can effectively reduce the level of traffic violations in the city of Semarang. The obstacle to implementation is the discovery of violations where the vehicle is not registered or does not have clear ownership identity. Based on direct research in the field, ETLE is seen by the public as very effective with a percentage of 80% and 20% less effective.